Sistem Informasi Geografi Berbasis Web Untuk Pemetaan Pariwisata Di Kota Dili - Didik Tristianto; Reinato Gomes (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
−Dili City is the capital city of Timor-Leste. Geographically Timor-Leste is located between the Australian continent in the south and the Indonesian archipelago in the west, north and east with land and sea boundaries. The tourism sector in the city of Dili is diverse with its natural uniqueness and is made by humans, but thus the efforts of the government have not been as much as possible to control in terms of facilities, entrance fees and transportation specifically to this place. The government in Dili City has carried out promotions through mass media via Facebook, Instagram. However, this method is not sufficient to inform tourism widely to local and foreign tourists. Therefore, through the design and manufacture of a tourism GIS, it is hoped that it can display an overview of the tourist map of Dili City. The system development method used in this study is the Waterfall method with several stages, namely design, analysis, coding and testing, implementation and maintenance with data requirements in accordance with the spatial data model in Geographic Information Systems. The map design displayed in this system uses Google Maps, the software used in building this application is PHP (Pear Hypertext Preprocessor) as a programming language, MySQL as a database server, Map GIS Marker, Visual Studio Code as code editing software